Tập hợp nội dung nhóm vấn đề đã được chất vấn tại các kỳ họp, phiên họp (nhiệm kỳ Quốc hội khóa XV) - Quốc hội Khoá XV (2023)
Toàn văn nội dung nhóm vấn đề đã được chất vấn tại các kỳ họp, phiên họp (nhiệm kỳ Quốc hội khóa XV).